2020
DOI: 10.1101/2020.10.10.331348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-dose intranasal administration of AdCOVID elicits systemic and mucosal immunity against SARS-CoV-2 in mice

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has highlighted the urgent need for effective preventive vaccination to reduce burden and spread of severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) in humans. Intranasal vaccination is an attractive strategy to prevent COVID-19 as the nasal mucosa represents the first-line barrier to SARS-CoV-2 entry before viral spread to the lung. Although SARS-CoV-2 vaccine development is rapidly progressing, the current intramuscular vaccines are designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…Following administration of NasoVAX, the vector infects epithelial cells of the nasal cavity and upper respiratory tract, where the antigen is expressed in the absence of viral replication. The expressed antigen can then be presented to the immune system through the HLA class I antigen processing machinery, leading to antiviral CD8+ T cell responses as observed in other studies [20]. The substantially greater T cell response associated with NasoVAX compared to the inactivated influenza vaccine comparator is consistent with the potential for Ad5 vectors to activate a systemic cellular immune response greater than other human adenovirus serotype vaccines [21].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Following administration of NasoVAX, the vector infects epithelial cells of the nasal cavity and upper respiratory tract, where the antigen is expressed in the absence of viral replication. The expressed antigen can then be presented to the immune system through the HLA class I antigen processing machinery, leading to antiviral CD8+ T cell responses as observed in other studies [20]. The substantially greater T cell response associated with NasoVAX compared to the inactivated influenza vaccine comparator is consistent with the potential for Ad5 vectors to activate a systemic cellular immune response greater than other human adenovirus serotype vaccines [21].…”
Section: Discussionsupporting
confidence: 72%
“…It is possible there may be a threshold for immune activation required to stimulate T cell responses, but additional studies will likely be required to understand the cellular response to NasoVAX. While not evaluated in this study, mucosal administration of Ad5 vectors promotes the establishment of resident memory T cells in preclinical models [ 20 ], a cell population of emerging importance in protection against invading pathogens, especially in viral infection [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies confirmed that immunization with a 10-fold lower dose (1 × 10 10 Ad5-S-nb2 particles) also conferred protection. In another approach, Ad5 vectors were engineered for the expression of the full-length SARS-CoV-2 S protein, the S1 domain and the RBD [ 39 ]. Intranasal immunization of mice with Ad5 expressing the SARS-CoV-2 S RBD (AdCOVID) elicited strong and focused RBD-specific induction of mucosal IgA, serum neutralizing antibodies and CD4 + and CD8 + T cells with Th1-like cytokine profiles.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Finally, intranasal SARS-CoV-2 vaccine delivery is a potential option [ 191 ]. For instance, intranasal administration of an Ad5-based vector expressing the SARS-CoV-2 S receptor binding domain (RBD) elicited strong neutralizing antibody responses [ 192 ] ( Table 3 ).…”
Section: Vaccines Against Covid-19mentioning
confidence: 99%